[Rezension von: Boyle, Brenda M., Looking Back on the Vietnam War] - Raphael-Hernandez, Heike (Journal of American history, 2018)
The editors of this collection have assembled eleven essays that take a fresh look at the legacy of the Vietnam War. Since the 1990s, one can observe a renewed